Про прогнозування розв’язкiв параболiчних рiвнянь за спостереженнями, розподiленими на системi поверхонь - Nakonechny, A. G.; Podlipenko, Yu. K.; Grishchuk, N. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Systems described by initial-boundary problems for parabolic equations of the second order with partial derivatives are considered. Based on observations of the solutions to these problems distributed in a finite time interval over a system of surfaces, minimax prediction estimates of functionals from the solutions are found. It is assumed that the right hand sides of the equations, boundary and initial conditions and also errors of measurements are not determined exactly: only the sets to which they belong are known. It is established that the determination of these estimates is reduced to solving some systems of integro-differential equations with partial derivatives and transmission conditions on the surfaces.